IMPACT ANALYSIS OF DIGITAL MARKETING: AN INDIAN PERSPECTIVE - Jeet Virendrabhai Madhani; Krunal Hareshkumar Rajyaguru (Jurnal Manajemen dan Kewirausahaan, 2020)
The increasing use of digital media by consumers, companies utilizes digital marketing to outreach their market segments. The purpose of this study is to determine marketing strategies commonly utilized in digital communication and identify the preferred by consumers which influences decision making. Consumers have been identified as a driving force for online shopping. While there have been numerous studies about digital advertising, there has been little academic research focused on type of digital marketing strategies are preferred and influences their consumer’s behavior. A survey of 225 consumes indicated a preference for side panel ads and email ads; they do not like pop – up advertising. If provided a personal benefit like discount or reward they will write an online product review.